Review paper on removal of heavy metal ions from industrial waste water effluent. Issue 1 (July 2021) - Mishra, Jaya; Saini, R; Singh, D
Abstract: Heavy metal ions is a major key of pollutions and it is one of the big environment issue today. To overcome with this problem the handling of metal ions is necessary. In recent research, there are various techniques that has been used to examin the metals ions and overview the methods also. The technologies involves are- ion-exchang, chemical precipitation, flotation, adsorption, membrane filtration, electro-chemical, coagulation-flocculation methods. It is find from experimental and literature survey article that membrane filtration, ion-exchange and adsorption are most common techniques used for the discourse of removal of metal ions from waste water effluent.